Wife's Income and Asset Position: A Comparative Study of Indonesia, Malaysia, Türkiye and Brunei Darussalam - Yanti Nasution, Zulhija; Kahar, Syadidul; Barus, Muhammad Irsan (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
This research aims to describe the position of the wife's income from the perspective of the law in Indonesia, Malaysia, Turkey, and Brunei Darussalam. The research method uses normative legal studies by comparing the four countries' legal views. The results showed that the wife's income assets in Indonesia and Turkey became joint assets and were divided equally upon separation. Meanwhile, in Malaysia and Brunei, the size of the wife's share when there is separation is determined by the amount of the wife's income.